Oral hygiene status, oral health-related behaviors, sleep, body mass index and dental caries prevalence of a sample aged five from Southwest China: a cross-sectional survey - Xiaoqin Xu; Hongmei Zhang; Mingshan Liu; Guangyun Lai (BMC Public Health)
Abstract Background This study aimed to revisit the early childhood caries (ECC) prevalence among children aged 5 in Xiangyun to assess the impact of caries intervention implemented in the past several years and explore the association between sleep status, body mass index, and ECC among young children in Xiangyun for the first time. Methods A total of 954 children aged five in Xiangyun were selected between September and November 2023. This cross-sectional survey comprised a dental examination and an oral health-related questionnaire. The caries presence was recorded according to the dental examination standard of the WHO 2013 criteria. The oral hygiene status was evaluated using the Simplified Debris Index (DI-S). Parents completed questionnaires that included demographic variables, family socioeconomic status, oral health-related habits, children’s sleep status, children’s birth weight, current height and weight. The statistical analysis was conducted using SPSS software. The chi-square test and logistic regression analysis identified significant variables associated with the prevalence of ECC. Statistical significance was set at a P-value of 0.05. Results Data from 45 incomplete questionnaires were removed from the analysis due to missing information. The ECC prevalence of 909 children consisting of 460 males and 449 females was 75.03%, with a mean dmft of 4.7 ± 4.6. Neither the sleep status nor the body mass index showed an association with the caries prevalence (P > 0.05). Logistic regression analysis showed that the most significantly associated factors were: the family income less than 6,000 Yuan, consuming desserts/cookies at least once a day, eating snacks without toothbrushing before bed, brushing teeth independently, having poor oral hygiene status and the use of fluoride toothpaste. Conclusions The prevalence of caries among 5-year-old children in Xiangyun remains higher than the national average in China. This higher prevalence is primarily associated with family income, several oral-health-related habits, and poor oral hygiene status, but not with sleep status or body mass index. In response, the local government should prioritize enhancing access to preventive oral care for children from impoverished families. Additionally, efforts should be made to encourage parents to supervise their children’s toothbrushing, improve their children’s oral hygiene, and correct harmful habits, such as eating snacks without brushing their teeth before bed in the future.